(untitled) (Heteroglossia – studia kulturoznawczo-filologiczne, 2022)
The aim of the article is to analyze the phenomenon of change in the process of faith and practices of Poles on the basis of the CBOS Research Communication Religiousness of young people against the background of the general public, published in November 2021 in relation to the process of mediatization of religion. The analytical-synthetic method and the non-media-centric approach were used. The analysis of the CBOS report on changes in the process of faith and practices of Poles made it possible to notice unprecedented changes in this area in the two youngest age cohorts. The main reasons for the decline in religious beliefs and practices, especially of the youngest Poles, go beyond the impact of the COVID-19 pandemic.